Fiscal Monitor, October 2019 : How to Mitigate Climate Change. (Fiscal Monitor; Fiscal Monitor ;, 2019)
This report emphasizes the environmental, fiscal, economic, and administrative case for using carbon taxes, or similar pricing schemes such as emission trading systems, to implement climate mitigation strategies. It provides a quantitative framework for understanding their effects and trade-offs with other instruments and applies it to the largest advanced and emerging economies. Alternative approaches, like 'feebates' to impose fees on high polluters and give rebates to cleaner energy users, can play an important role when higher energy prices are difficult politically. At the international level, the report calls for a carbon price floor arrangement among large emitters, designed flexibly to accommodate equity considerations and constraints on national policies. The report estimates the consequences of carbon pricing and redistribution of its revenues for inequality across households. Strategies for enhancing the political acceptability of carbon pricing are discussed, along with supporting measures to promote clean technology investments.